1991
DOI: 10.1073/pnas.88.19.8806
|View full text |Cite
|
Sign up to set email alerts
|

Nonnucleoside reverse transcriptase inhibitors that potently and specifically block human immunodeficiency virus type 1 replication.

Abstract: Certain bis(heteroaryl)piperazines (BHAPs) are potent inhibitors of the human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) at concentrations lower by 2-4 orders of magnitude than that which inhibits normal cellular DNA polymerase activity. Combination of a BHAP with nucleoside analog IIV-1 RT inhibitors suggested that together these compounds inhibited RT synergistically. In three human lymphocytic cell systems using several laboratory and clinical HIV-1 isolates, the BHAPs blocked HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
154
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(158 citation statements)
references
References 25 publications
3
154
0
1
Order By: Relevance
“…In contrast to the classical RT inhibitors such as phosphonoformic acid (PFA) and 3'-azido-3'-deoxythymidine (AZT) 5'-triphosphate, TIBO and HEPT inhibit HIV-1 RT, but not HIV-2 RT. The more recently developed dipyridodiazepinones, pyridinones and bis(hetero-aryl)piperazines share this property (Merluzzi et al, 1990;Goldman et al, 1991;Romero et al, 1991). The HIV-l-specific RT inhibitors are ineffective not only against HIV-2 RT, but also against the RTs of avian myeloblastosis virus, Moloney murine leukaemia virus, SIV [from macaques (SlVmac)] and feline leukaemia virus (Merluzzi et al, 1990;Debyser et al, 1991;Goldman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the classical RT inhibitors such as phosphonoformic acid (PFA) and 3'-azido-3'-deoxythymidine (AZT) 5'-triphosphate, TIBO and HEPT inhibit HIV-1 RT, but not HIV-2 RT. The more recently developed dipyridodiazepinones, pyridinones and bis(hetero-aryl)piperazines share this property (Merluzzi et al, 1990;Goldman et al, 1991;Romero et al, 1991). The HIV-l-specific RT inhibitors are ineffective not only against HIV-2 RT, but also against the RTs of avian myeloblastosis virus, Moloney murine leukaemia virus, SIV [from macaques (SlVmac)] and feline leukaemia virus (Merluzzi et al, 1990;Debyser et al, 1991;Goldman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several classes of nonnucleoside reverse transcriptase inhibitors (NNRTIs), which are also potent inhibitors of HIV-1 replication in cell culture, have been identified. These include the pyridinone L-697,661 [1], nevirapine [2,3], the TIBO derivatives [4], TSAO [5], HEPT [6], inophyllums [7], and the BHAPs [8,9]. Despite their structural dissimilarity, they are all relatively inactive against HIV-2 RT and, in general, are non-competitive with respect to substrates.…”
Section: Introductionmentioning
confidence: 99%
“…I), all of the drugs are highly specific for HIV-I; i.e., they do not inhibit a variety of other DNA polymerases including HIV-RT type 2. Although most of the drugs (such as nevirapine and the TlBO derivatives) appear to be mechanistically noncompetitive for primer, template, and nucleotide (Kopp et al, 1991;Romero et al, 1991), at least one inhibitor (HEPT) has been reported to be competitive with respect to the natural substrate dTTP (Baba et al, 1991). In addition, nonnucleoside inhibitors show a lower cellular toxicity than nucleoside inhibitors (Pauwels et al, 1990; Romero et al, 1991).…”
mentioning
confidence: 99%